Verrucous carcinoma of the oesophagus is a genetically distinct subtype of oesophageal squamous cell carcinoma. Issue 4 (8th July 2021) - Isidro, Raymond A; Dong, Fei; Hornick, Jason L; Wee, Jon O; Agoston, Agoston; Patil, Deepa T.; Deshpande, Vikram; Zhao, Lei
Abstract : Aims: Oesophageal verrucous carcinoma (VSCC) is a rare and morphologically distinct type of oesophageal squamous cell carcinoma (SCC). Diagnosing VSCC on biopsy material is challenging, given the lack of significant atypia and the presence of keratinising epithelium and exophytic growth. The molecular pathogenesis of VSCC remains unclear. The aim of this study was to characterise the genomic landscape of VSCC in comparison to conventional oesophageal SCC. Methods and results: Three cases of VSCC from the Brigham and Women's Hospital pathology archive were identified. Formalin‐fixed, paraffin‐embedded (FFPE) tumour tissue was used for p16 immunohistochemistry (IHC), high‐risk human papillomavirus (HPV) in‐situ mRNA hybridisation (ISH) and DNA isolation. Tumour DNA was sequenced using a targeted massively parallel sequencing assay enriched for cancer‐associated genes. Three additional cases of VSCC were identified by image review of The Cancer Genome Atlas (TCGA) oesophageal SCC cohort. VSCC cases were negative for p16 IHC and high‐risk HPV ISH. TP53 mutations ( P  < 0.001) and copy number variants (CNVs) for CDKN2A ( P  < 0.001), CDKN2B ( P  < 0.01) and CCND1 ( P  < 0.01) were absent in VSCC and significantly less frequent in comparison to conventional SCC. Five VSCC cases featured SMARCA4 missense mutations or in‐frame deletions compared to only four of 88 conventional SCC cases ( P  < 0.001). VSCC featured driver mutations in PIK3CA, HRAS and GNAS . Recurrent CNVs were rare in VSCC. Conclusions: VSCC is not only morphologically but also genetically distinct from conventional oesophageal SCC, featuring frequent SMARCA4 mutations and infrequent TP53 mutations or CDKN2A/B CNVs. Molecular findings may aid in establishing the challenging diagnosis of VSCC. Abstract :